Integrated transcriptome and metabolome analysis of photoperiod effects on testosterone secretion in ChaHua chicken No.2 Roosters - Mengqian Liu; Lei Tan; Xinlu Li; Haojie Li; Yong Zhang; Xiannian Zi; Changrong Ge; Kun Wang (Poultry Science)
This study investigated the impact of light duration on Testosterone secretion in Chahua No.2 roosters, utilizing combined Transcriptome and Metabolome analyses to uncover critical genes, Metabolites, and signaling pathways. We randomly selected 240 Chahua No.2 roosters at 42 days old and divided them into four groups: simulated natural light (Ⅰ), 12L:12D (Ⅱ), 16L:8D (Ⅲ), and 20L:4D (Ⅳ), each group has 6 replicates, with 10 chickens per replicate. Blood samples were collected at 91 and 140 days post-hatch to measure Testosterone levels. Results showed that at 91 days, group Ⅳ had significantly higher Testosterone levels than groups Ⅰ, Ⅱ, and Ⅲ (P < 0.01), with group Ⅲ also higher than groups Ⅰ (P < 0.01) and Ⅱ (P < 0.05). By 140 days, group Ⅳ maintained significantly higher Testosterone than groups Ⅰ and Ⅱ (P < 0.01) and higher than group Ⅲ (P < 0.05), while group Ⅲ was also elevated compared to groups Ⅰ and Ⅱ (P < 0.05). Testicles Transcriptomics analysis revealed 891 differentially expressed genes, including 479 down-regulated and 412 up-regulated genes. Key signaling pathways identified included Steroid Hormone Biosynthesis, Cytochrome P450, and retinol metabolism. Testicles Metabolomics analysis identified 174 differential Metabolites, with 91 up-regulated and 83 down-regulated, focusing on pathways like Amino Sugar Metabolism and Tryptophan Metabolism. Integrated analysis pinpointed 19 common signaling pathways, with the top ten including Cytochrome P450, tyrosine metabolism, and amino acid biosynthesis. Our findings indicate that extending light duration enhances Testosterone secretion in roosters. Through comprehensive transcriptomic and metabolomic analyses, we established that pathways associated with steroid hormone synthesis and Cytochrome P450 play a crucial role in light duration-regulated Testosterone secretion, highlighting key genes such as CYP11A1, CYP17A1, and HSD3B1, alongside Metabolites like ergosterol-5,7,22,24(28)-tetraene-3beta-alcohol.